Prasugrel vs clopidogrel in patients with acute coronary syndrome undergoing percutaneous coronary intervention: a model-based cost-effectiveness analysis for Germany, Sweden, the Netherlands, and Turkey. Issue 4 (April 2013) - Davies, Andrew; Bakhai, Ameet; Schmitt, Claude; Barrett, Annabel; Graham-Clarke, Peita; Sculpher, Mark
Abstract Objective: To evaluate the long-term cost-effectiveness of 12-months treatment with prasugrel vs clopidogrel from four European healthcare systems' perspectives (Germany, Sweden, the Netherlands, and Turkey). Methods: In the TRITON-TIMI 38 trial, patients with an acute coronary syndrome (ACS) undergoing percutaneous coronary intervention (PCI) were treated with prasugrel or clopidogrel. Prasugrel reduced the composite end-point (cardiovascular death, MI, or stroke), but increased TIMI major bleeding. A Markov model was constructed to facilitate a lifetime horizon for the analysis. A series of risk equations constructed using individual patient data from TRITON-TIMI 38 was used to estimate risks of clinical events. Quality-adjusted life-years (QALYs) were derived by weighting survival time by estimates of health-related quality-of-life. Incremental cost-effectiveness is presented based on differences in treatments' mean costs and QALYs for the licensed population in TRITON-TIMI 38, and the sub-groups of UA-NSTEMI, STEMI, diabetes, and the 'core clinical cohort' (<75 years, ≥60 kg, no history of stroke or TIA). Results: Mean cost of study drug was €364 (Turkey) to €818 (Germany) higher for prasugrel vs clopidogrel. Rehospitalization costs at 12 months were lower for prasugrel due to reduced rates of revascularization, although hospitalization costs beyond 12 months were higher due to longer life expectancy associated with lower rates of non-fatal MI in the prasugrel group. The incremental cost per QALY saved with prasugrel in the licensed population ranged from €6520 (for Sweden) to €14, 350 for (Germany). Prasugrel's cost per QALY was more favourable still in the STEMI and diabetes sub-groups of the licensed population. Limitations: Probabilistic analyses of the whole trial population is impractical due to the number of individual patient profiles over which population level results are calculated. Conclusion: Among patients undergoing PCI for ACS, treatment with prasugrel compared with clopidogrel resulted in favourable cost-effectiveness profiles from these healthcare systems' perspectives.